Potential for planting rubber trees for timber production - Mohd. Lokmal Ngah; Ahmad D; Ibrahim Z (In: Proceedings of the International Forum on Investment Opportunities in the Rubber Wood Industry, 20-22 September 1993, Kuala Lumpur, Malaysia, pp.25-29., 1993)
The paper explores the potential of planting rubber trees for timber production. The supply and demand of Rubberwood looks favourable till the year 2000 after which the planting of rubber trees is essential to ensure future supply. Results of clone trials of rubber are presented with the future outlook of the potential of planting rubber trees for timber production.
Keywords: Rubberwood